Case Report: ANXA2 Associated Life-Threatening Coagulopathy With Hyperfibrinolysis in a Patient With Non-APL Acute Myeloid Leukemia - Ruhnke, Leo; Stölzel, Friedrich; Wagenführ, Lisa; Altmann, Heidi; Platzbecker, Uwe; Herold, Sylvia; Rump, Andreas; Schröck, Evelin; Bornhäuser, Martin; Schetelig, Johannes; von Bonin, Malte (Frontiers in Oncology, 2021)
Patients with acute promyelocytic leukemia (APL) often present with potentially life-threatening hemorrhagic diathesis. The underlying pathomechanisms of APL-associated coagulopathy are complex. However, two pathways considered to be APL-specific had been identified: 1) annexin A2 (ANXA2)-associated hyperfibrinolysis and 2) podoplanin (PDPN)-mediated platelet activation and aggregation. In contrast, since disseminated intravascular coagulation (DIC) is far less frequent in patients with non-APL acute myeloid leukemia (AML), the pathophysiology of AML-associated hemorrhagic disorders is not well understood. Furthermore, the potential threat of coagulopathy in non-APL AML patients may be underestimated. Herein, we report a patient with non-APL AML presenting with severe coagulopathy with hyperfibrinolysis. Since his clinical course resembled a prototypical APL-associated hemorrhagic disorder, we hypothesized pathophysiological similarities. Performing multiparametric flow cytometry (MFC) and immunofluorescence imaging (IF) studies, we found the patient's bone-marrow mononuclear cells (BM-MNC) to express ANXA2 - a biomarker previously thought to be APL-specific. In addition, whole-exome sequencing (WES) on sorted BM-MNC (leukemia-associated immunophenotype (LAIP)1: ANXAlo, LAIP2: ANXAhi) demonstrated high intra-tumor heterogeneity. Since ANXA2 regulation is not well understood, further research to determine the coagulopathy-initiating events in AML and APL is indicated. Moreover, ANXA2 and PDPN MFC assessment as a tool to determine the risk of life-threatening DIC in AML and APL patients should be evaluated.